Jago kuasai bahasa Prancis / Triastutik, Adis Mila Firdasari; editor, Jarwanto S. Noe - TRIASTUTIK , 1993-; Adis Mila Firdasari; Jarwanto S. Noe (Pustaka Baru Press, 2015)
vi, 250 hlm. : ilus. ; 22 cm.